Travel lifestyles and outbound tourism intentions of young Malaysians - Cheah, Swee Ting; Lim, Khong Chiu; Kayat, Kalsom (Scientific & Academic Publishing Co., 2015)
The young travellers’ segment is an emerging market for today’s travel and hospitality industry. Yet, there is negligence in this lucrative market segment. It is common that most countries including Malaysia fail to collect statistics regarding young travelers’ holiday patterns. The study of past literature on tourists’ holiday decision paves the way to explore the young Malaysians’ travel lifestyles and outbound tourism intentions. Although most of the findings are helpful to understand the young travelers market, the related study of young Malaysian travelers is limited. This study intends to fill the gap by examining the relationship between travel lifestyles and outbound tourism intentions of young Malaysians. Hence, this will be significantly helpful for marketers in developing positioning strategies in order to provide a total tourism experience for the potential travelers.